2021
DOI: 10.1088/1742-5468/abf7b5
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic dynamics and superstatistics of the many-particle kappa distribution

Abstract: The diffusion of particles with kappa distributed velocities is strongly influenced by statistical correlations. We argue that the consistent way to deduce the diffusion laws of any one degree of freedom is to analyze the simultaneous diffusion of virtually infinite correlated degrees of freedom. This is done by deriving the diffusion laws (I) by utilizing the superstatistics interpretation of the kappa distribution and averaging the usual Brownian motions correlators over the super-ensemble of fluctuating tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Eq. ( 14) has applications in different scenarios, e.g., in percolation of gases through porous media [61], thin saturated regions in porous media [62], nonextensive scaling law in confined granular media [63], and is also object of current investigation [64][65][66]. Moreover, the nonlinear Fokker-Planck equation extends the porous medium diffusion equation to generalized scenarios of statistical mechanics [67][68][69][70][71][72].…”
Section: B Porous Media Diffusionmentioning
confidence: 99%
“…Eq. ( 14) has applications in different scenarios, e.g., in percolation of gases through porous media [61], thin saturated regions in porous media [62], nonextensive scaling law in confined granular media [63], and is also object of current investigation [64][65][66]. Moreover, the nonlinear Fokker-Planck equation extends the porous medium diffusion equation to generalized scenarios of statistical mechanics [67][68][69][70][71][72].…”
Section: B Porous Media Diffusionmentioning
confidence: 99%
“…[9] The diffusion of particles with kappa-distributed velocities is strongly influenced by statistical correlations. [10] A lot of observations have shown that ultra-hot particles with non-Maxwell distribution in the form of power law exist widely in space plasma. The plasma systems with superthermal electrons are well described by the kappa distribution.…”
Section: Introductionmentioning
confidence: 99%